Therapeutic Community: Pendampingan Rehabilitasi NAPZA dengan Memberdayakan Komunitas - Susanto, Shobri Firman; Widyawari, Monica; Sari, Anisa Yunita; Rozi, Muhamad Fahrur; Raniya, Pudyas Tataquna (Universitas Negeri Padang, 2024)
Abstracts must be factual and concise. Must By broadening the scope, the aim of this research is to find innovative and sustainable solutions to the challenges faced by drug abusers and rehabilitation institutions in the process of assisting the rehabilitation of drug abusers. In addition, this research also seeks to provide practical guidance for practitioners in designing rehabilitation programmes with the concept of Therapeutic Community that are effective in helping drug-dependent individuals become fully recovered. This research uses a qualitative approach, an assessment of an event, a view of the world, an opportunity to use a theory, and collect data from the meaning of individuals or groups related to social or human problems. From the results of this study, it can be concluded that the application of the therapeutic community concept in drug rehabilitation assistance has had a positive impact in empowering communities in Indonesia. Through spiritual, social, life skills training, and group assistance, drug abusers receive holistic support.Keywords: Therapeutic Community, Drug Rehabilitation Assistance, Empowering the Community..ABSTRAKDengan memperluas cakupan maka tujuan penelitian ini diharapkan akan ditemukan solusi yang inovatif dan berkelanjutan dalam menghadapi tantangan yang dihadapi oleh penyalahguna NAPZA dan lembaga rehabilitasi dalam proses pendampingan rehabilitasi penyalahguna NAPZA. Selain itu, penelitian ini juga berusaha untuk menyediakan panduan praktis bagi para praktisi dalam mendesain program rehabilitasi dengan konsep Therapeutic Community yang efektif guna membantu individu yang ketergantungan NAPZA menjadi sepenuhnya pulih. Penelitian ini menggunakan pendekatan kualitatif, penaksiran dari suatu kejadian, pandangan tentang dunia, kesempatan penggunaan suatu teori, dan mengumpulkan data dari makna individu atau kelompok yang berkaitan dengan masalah sosial atau manusia. Dari hasil penelitian ini, dapat disimpulkan bahwa penerapan konsep therapeutic community dalam pendampingan rehabilitasi NAPZA telah memberikan dampak positif dalam memberdayakan komunitas di Indonesia. Melalui pendampingan spiritual, sosial, pelatihan kecakapan hidup, dan kelompok, penyalahguna NAPZA mendapatkan dukungan yang holistik.Kata Kunci: Therapeutic Community, Pendampingan Rehabilitasi NAPZA, Memberdayakan Komunitas.